Delivery luteolin with folacin-modified nanoparticle for glioma therapy - Wu C (Dove Medical Press, 2019)
Cong Wu, Qian Xu, Xinyue Chen, Jiagang Liu Department of Neurosurgery, West China Hospital, West China Medical School, Sichuan University, Chengdu 610041, People’s Republic of ChinaCorrespondence: Jiagang LiuDepartment of Neurosurgery, West China Hospital, West China Medical School, Sichuan University, Chengdu 610041, People’s Republic of ChinaTel +86 288 542 2136Fax +86 288 550 2796Email jiagang_liu@163.comBackground: Glioblastoma mutliforme is the most common and has the poorest prognosis of any malignant tumor of the central nervous system. Luteolin, the most abundant xanthone extracted from vegetables and medicinal plants, has been shown to have treatment effects in various cancer cell types. Luteolin is however, hydrophobic and has poor biocompatibility, which leads to low bioavailability.Patients and methods: In this study, folic acid modifiedpoly(ethylene glycol)-poly(e-caprolactone) (Fa-PEG-PCL) nano-micelles was used to encapsulate the luteolin, creating luteolin loaded PEG-PCL (Lut/Fa-PEG-PCL) micelles to treat glioma both in vitro and in vivo.Results: When compared with the free luteolin and Lut/MPEG-PCL, Lut/Fa-PEG-PCL induced a significant cell growth inhibition and more apoptosis of GL261 cells both in vitro and in vivo. The safety assessment also showed no obvious side effects were observed in mice which were administrated with free luteolin or Lut/MPEG-PCL and Lut/Fa-PEG-PCL.Conclusion: These results suggested Lut/Fa-PEG-PCL may be used as an excellent intravenously injectable formulation for the treatment and chemoprevention.Keywords: luteolin, PEG-PCL, glioma, folic acid, apoptosis